Qiṣṣat Rūbinṣun Kurūzī ... - Defoe, Daniel ([publisher not identified], 1835)
Translation, abridged, of the first part of Robinson Crusoe, into fairly classical Arabic.
Translation, abridged, of the first part of Robinson Crusoe, into fairly classical Arabic.
c.2: For information regarding an earlier Arabic translation of manuscript note on leaf preceding frontispiece, and Ullrich, H. Robinson und Robinsonaden.
c.2: Lacking one plate.
c.1: With variant plates.